Hubungan Jaringan Internet terhadap Karakter Kedisiplinan Mahasiswa PGSD STKIP Al Hikmah Surabaya Selama Pembelajaran Daring - Dussawal , Wahed; Widodo, Slamet (Scholarly Journal of Elementary School, 2022)
Since February 2020 Indonesia had hited by Covid-19, transmission this virus is very fast and victim total increase every day. It is had impact that government should published a policy about social restriction. All activities are limited belonging on education. Learning in the campus also did onlinely. Since online learning is done, many students have problems due to unstable connection that decrease on discipline character of students. This research aim to know relation between internet connections to discipline character of students. Subject of research are used with involve 22 students of primary school teacher candidate of Al Hikmah Teacher Institute, meanwhile data analize technique utilize quantitative data analize technique. The result of this study showed that there are correlations significancies between intetnet connections to discipline character of students.